Evaluation of the ability of endemic herbal extracts to bio-control some plant pathogenic bacteria: (Araceae of Libya). - abdulrraziq, Ahmed A.; salih, Sami M. (Scientific Journal for Faculty of Science-Sirte University, 2024)
Potentially control of plant diseases in the future can occur by utilizing endemic plant extracts to provide biotic and abiotic environmental conditions that are beneficial for host development and growth which are adverse to pathogen reproduction and evolution. The present study reports the antibacterial activities of three species of endemic herbs of Araceae. The antibacterial activity was determined by methanol and acetone extraction of aerial and underground parts of three endemic herbaceous species in Libya; Arisarum vulgari, Arum cyreniacum and Biarum bovei. The test was conducted by Screening using the disc diffusion technique, against Two various species of plant-pathogenic bacteria; Agrobacterium spp. and Erwinia spp. According to this study, the most effective way to manage plant-pathogenic bacteria was tuber extracts, especially B. bovei tubers. A. cyreniacum tuber extracts also showed good efficacy, while A. vulgaris extracts were the least effective. On the other hand, the majority of the examined extracts had the greatest impact on Erwinia spp. This is the first report to highlight the potential of all species of endemic herbs of Araceae family of Libya in the bio-control of plant pathogens. Thus, endemic herbs of Araceae can be considered to possess strong germicidal properties against plant disease-causing Agrobacterium spp.and Erwinia spp.